Lãnh đạo chuyên quyền và hạnh phúc chủ quan của nhân viên: Vai trò của sự lấy lòng và lòng tự trọng - Bùi Thị Kim, Hoàng; Nguyễn Thị Mai, Trang; Nguyễn Thị Mai, Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study examines the impact of despotic leadership on employees' subjective well-being through ingratiation behavior. Additionally, it investigates whether self-esteem moderates the positive relationship between despotic leadership and ingratiation. Data were collected from 215 employees working in the telecommunications sector in Vietnam, and partial least squares structural equation modeling (PLS-SEM) was employed to test the hypotheses. The results supported the mediating effect of ingratiation between despotic leadership and subjective well-being. Furthermore, the effect of despotic leadership on ingratiation was found to be weaker among employees with higher levels of self-esteem. This study makes significant contributions to leadership theory and organizational psychology and offers practical implications for the management and development of human resources within organizations
Keywords: Despotic leadership; Ingratiation; Subjective well-being; Self-esteem